Insects, worlds, and the poetic in Coetzee's writing. Issue 3 (15th April 2016) - Egerer, Claudia
Abstract : J. M. Coetzee's literary universe creates a space for creatures often thought so insignificant that they are mostly overlooked or, if noticed at all, discarded as useless pests. In his writing, we repeatedly experience moments of wonder when insects take centre-stage, touching characters and readers alike with awe at their power of transformation. These moments are like poetic epiphanies, flashes into worlds otherwise closed to human experience. But Coetzee's imagining of insects vis-à-vis his characters also challenges the way we think about the world in general and the environment in particular, not least our own role in it. Martin Heidegger is but one in a long line of philosophers at pains to reinforce the boundary drawn between human and animal, arguing that the animal, unlike the human, only has limited access to its surroundings. Yet it is also Heidegger who is early in his recognition of the repercussions of human arrogance on the environment. Zoologist Jakob von Uexküll's research into insect worlds challenges the understanding that the human has access to the world in its entirety, stressing the relational aspect that all living beings have with their surroundings, their Umwelt, the human animal included. Agamben brings to this the idea that all animals, even insects, experience a certain openness within their environment, a capacity that Heidegger granted only to the human. This diversity of environmental worlds shaped by species-specific needs and abilities suggests that humans are subject to the same mechanisms that limit access to the Umwelt of other creatures, from which follows that any attempt to know another being's Umwelt would involve a venture into territory which requires different and novel ways of seeing. Literature is the space which invites us into unknowable worlds and supplies us with the tongue to touch on the not-yet-formulated. Coetzee's poetic imagination draws our attention to what I would like to describe as an extraordinary rapport between insects and the poetic in his texts, both marked by being at once recognisable yet infinitely other, providing us with rare glimpses into unknowable worlds and our own implication in them.